ANALISIS PENCURIAN DENGAN KEKERASAN DALAM PERSPEKTIF KRIMINOLOGI DI WILAYAH HUKUM KEPOLISIAN RESORT PALU - Ahmad Allang (Maleo Law Journal, 2017)
The theft of violence in Palu from 2014 to 2016 was recorded 582, each year experiencing an average increase of 29.79%, succeeded in P21 Palu Resort Police 79.21%. The cause is bad perpetrators, clothing and urgent needs because they are not permanent workers but casual workers and even unemployed, and negligence of victims. The pattern is performed when the victim is unable to keep his or her possessions especially during bad weather, the modus operandi of the perpetrator performs threats with firearms or sharp weapons, seizes the victim's bag, gropes the victim's vehicle, pulls the victim's clothes down from his vehicle. The need for the government to expand / create new jobs as an effort to improve the prosperity of the people of Palu City.Keywords: Theft With Violence, Criminology